Combined effect of Lactobacillus acidophilus and β-cyclodextrin on serum cholesterol in pigs. Issue 1 (15th October 2015) - Alonso, L.; Fontecha, J.; Cuesta, P.
Abstract: A total of twenty-four Yorkshire gilt pigs of 6–7 weeks of age were used in a 2×2 factorial experiment to determine the individual and combined effects of the inclusion of two dietary factors (cholesterol rich, 3 % β -cyclodextrin (BCD) and Lactobacillus acidophilus cultures) on total cholesterol and LDL-cholesterol levels in blood serum. Pigs were assigned randomly to treatment groups ( n 6). Total serum cholesterol concentrations decreased after 3 weeks in all the experimental treatment groups, including diets with BCD, L . acidophilus or both. Similar trends were observed for serum LDL-cholesterol concentrations among the experimental treatments. No statistically significant differences from the control group were observed in either total serum cholesterol or LDL-cholesterol concentrations ( P <0·05) for each of the individual treatment groups: BCD or L . acidophilus . However, significant differences in total serum cholesterol concentrations were observed when comparing the combined treatment group (BCD and L . acidophilus ) with the control group, which consisted of a basal diet and sterile milk. The combined treatment group exhibited 17·9 % lower total serum cholesterol concentration after 3 weeks. Similar significant differences were observed when comparing the combined effect experimental group with the control group after 3 weeks. The combined treatment group exhibited 27·9 % lower serum LDL-cholesterol concentrations.